2019
DOI: 10.1016/j.pgeola.2018.02.005
|View full text |Cite
|
Sign up to set email alerts
|

The Quaternary rivers of the Jurassic Coast region: From the Neogene to the Anthropocene

Abstract: The Jurassic Coast World Heritage Sites (JCWHS) is not only a 95 km long coastline and remarkable Mesozoic geological section, but also a slice through a Quaternary landscape. For the majority of the last two million years this landscape lay in the periglacial zone, just south of a waxing and waning ice margin and just north of an Atlantic inlet which eventually became the English Channel. This paper reviews how the previous landscape inherited from the Cenozoic, was modified through uplift, climatically drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The publications that directly link geoheritage to the Anthropocene remain very few [42][43][44][45][46][47]. Some articles focus on specific issues and others relate two ideas in an occasional manner.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The publications that directly link geoheritage to the Anthropocene remain very few [42][43][44][45][46][47]. Some articles focus on specific issues and others relate two ideas in an occasional manner.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Pica et al [43] stressed a still limited interest of Anthropocene researchers in urban geomorphological heritage, although the latter provides excellent evidence of characteristic features such as specific deposits of the newlyproposed epoch. Brown et al [44] reviewed the alluvial record of the Jurassic Coast World Heritage Sites and concluded that some landforms and sediments reflect human activity in the Anthropocene and, thus, this globally-ranked geoheritage site can contribute to the knowledge of this interval of the geological time.…”
Section: Literature Overviewmentioning
confidence: 99%